Genome sequence of the banana aphid, Pentalonia nigronervosa Coquerel (Hemiptera: Aphididae) and its symbionts - Mathers, T.C.; Mugford, S.T.; Hogenhout, S.A.; Tripathi, L. (Oxford University Press, 2020)
The banana aphid, Pentalonia nigronervosa Coquerel (Hemiptera: Aphididae), is a major pest of cultivated bananas (Musa spp., order Zingiberales), primarily due to its role as a vector of Banana bunchy top virus (BBTV), the most severe viral disease of banana worldwide. Here, we generated a highly complete genome assembly of P. nigronervosa using a single PCR-free Illumina sequencing library. Using the same sequence data, we also generated complete genome assemblies of the P. nigronervosa symbiotic bacteria Buchnera aphidicola and Wolbachia. To improve our initial assembly of P. nigronervosa we developed a k-mer based deduplication pipeline to remove genomic scaffolds derived from the assembly of haplotigs (allelic variants assembled as separate scaffolds). To demonstrate the usefulness of this pipeline, we applied it to the recently generated assembly of the aphid Myzus cerasi, reducing the duplication of conserved BUSCO genes by 25%. Phylogenomic analysis of P. nigronervosa, our improved M. cerasi assembly, and seven previously published aphid genomes, spanning three aphid tribes and two subfamilies, reveals that P. nigronervosa falls within the tribe Macrosiphini, but is an outgroup to other Macrosiphini sequenced so far. As such, the genomic resources reported here will be useful for understanding both the evolution of Macrosphini and for the study of P. nigronervosa. Furthermore, our approach using low cost, high-quality, Illumina short-reads to generate complete genome assemblies of understudied aphid species will help to fill in genomic black spots in the diverse aphid tree of life.